2012
DOI: 10.1016/j.ahj.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of QRS morphology on clinical event reduction with cardiac resynchronization therapy: Meta-analysis of randomized controlled trials

Abstract: Background Cardiac resynchronization therapy (CRT) is effective in reducing clinical events in systolic heart failure patients with a wide QRS. Previous retrospective studies suggest only patients with QRS prolongation due to a left bundle-branch block (LBBB) benefit from CRT. Our objective was to examine this by performing a meta-analysis of all randomized controlled trials of CRT. Methods Systematic searches of MEDLINE and the Food and Drug Administration official website were conducted for randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
1
20

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(180 citation statements)
references
References 29 publications
10
149
1
20
Order By: Relevance
“…In addition, the sub‐study of the Multicenter Automatic Defibrillator Implantation Trial‐Cardiac Resynchronization Therapy (MADIT‐CRT) trial, including 1817 patients with sinus rhythm at baseline ECG, showed that the presence of LBBB morphology was associated with a 53% reduction in the risk of heart failure events or all‐cause mortality of patients randomized to CRT with defibrillator compared with patients treated with implantable cardioverter defibrillator (ICD) alone whereas patients with non‐LBBB QRS morphology did not show clinical benefit from CRT 7. Subsequent meta‐analysis pooling data from 5356 patients enrolled in four randomized trials showed that LBBB morphology was associated with significant reduction in the composite adverse clinical events of patients treated with CRT (risk ratio 0.64, 95% CI 0.52–0.77; P  < 0.0001) whereas patients with non‐LBBB configuration failed to show clinical benefit 9. Recently, the analysis of data from 31 892 heart failure patients treated with CRT (76% with LBBB QRS morphology) included in the National Cardiovascular Data Registry and the ICD registry showed that after a median follow‐up of 3 years, patients with LBBB morphology had 24% lower mortality risk than patients with non‐LBBB morphology (HR 0.76, 95% CI 0.72–0.80; P  < 0.001) 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the sub‐study of the Multicenter Automatic Defibrillator Implantation Trial‐Cardiac Resynchronization Therapy (MADIT‐CRT) trial, including 1817 patients with sinus rhythm at baseline ECG, showed that the presence of LBBB morphology was associated with a 53% reduction in the risk of heart failure events or all‐cause mortality of patients randomized to CRT with defibrillator compared with patients treated with implantable cardioverter defibrillator (ICD) alone whereas patients with non‐LBBB QRS morphology did not show clinical benefit from CRT 7. Subsequent meta‐analysis pooling data from 5356 patients enrolled in four randomized trials showed that LBBB morphology was associated with significant reduction in the composite adverse clinical events of patients treated with CRT (risk ratio 0.64, 95% CI 0.52–0.77; P  < 0.0001) whereas patients with non‐LBBB configuration failed to show clinical benefit 9. Recently, the analysis of data from 31 892 heart failure patients treated with CRT (76% with LBBB QRS morphology) included in the National Cardiovascular Data Registry and the ICD registry showed that after a median follow‐up of 3 years, patients with LBBB morphology had 24% lower mortality risk than patients with non‐LBBB morphology (HR 0.76, 95% CI 0.72–0.80; P  < 0.001) 22.…”
Section: Discussionmentioning
confidence: 99%
“…However, the individual prognostic benefit is not consistent, and selection of patients who will benefit from CRT remains challenging. Sub‐analyses from randomized controlled trials and meta‐analyses pointed out that QRS duration and morphology are relevant for prognosis of patients treated with CRT 5, 6, 7, 8, 9. Patients with shorter QRS duration and/or non‐left bundle branch block (LBBB) morphology appear to benefit less than patients with longer QRS duration and/or LBBB morphology 5, 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Cardiac resynchronization therapy (CRT) has shown to be effective in reducing adverse events in LBBB patients. 28 The benefit of CRT in NOP-LBBB after TAVI is widely unknown. Meguro et al reported an effective CRT therapy for a patient with worse cardiac function with NOP-LBBB after TAVI.…”
Section: Permanent Pacemaker Implantation In New-onset Persistent Lefmentioning
confidence: 99%
“…However, sub-group analyses based on QRS morphology [30,31,56] and a metaanalysis [57] suggested that patients with complete LBBB showed a greater benefit on the composite of morbidity/mortality from CRT, compared with patients with non-specific intraventricular conduction delay or right bundle branch block. Based on this evidence, current class I recommendations were restricted to patients with complete LBBB.…”
Section: Patient Selectionmentioning
confidence: 99%